Bioactive Glass Fiber-Reinforced Composite For Bone Regeneration - Ma'ruf, Mochammad Taha (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Bone regeneration remains a critical challenge in tissue engineering, with current solutions such as autografts and allografts facing limitations in availability, cost, and biocompatibility. Bioactive glass fiber-reinforced composites (BGFRC) have emerged as a promising alternative, combining the bioactivity of bioactive glass with the mechanical strength of fiber-reinforced materials.Methods: This literature review synthesizes findings from 46 recent journal articles and books on bioactive glass, bioactive glass fibers, and BGFRC. The review focuses on material composition, mechanical properties, fabrication techniques, and biological interactions. Key aspects include the role of bioactive glass in promoting osteointegration and the reinforcement provided by glass fibers to enhance mechanical performance.Results: BGFRC exhibits superior bioactivity by forming a hydroxyapatite layer upon exposure to physiological fluids, facilitating strong bonding with bone tissue. The release of therapeutic ions stimulates osteogenesis and angiogenesis, promoting bone regeneration. The incorporation of glass fibers significantly improves mechanical properties, including compressive strength and fracture toughness, making BGFRC suitable for load-bearing applications. Advancements in fabrication techniques such as sol-gel processing and 3D printing allow for precise control over porosity and degradation rates, optimizing scaffold design for clinical applications.Conclusion: BGFRC represents a highly promising material for bone tissue engineering due to its enhanced bioactivity, mechanical reinforcement, and biocompatibility. Future research should focus on optimizing composite formulations and exploring clinical applications to further validate their effectiveness in bone regeneration.